Sistem Penghitung Jeruk Matang pada Kebun berdasarkan Hue, Saturation dan Chrominance-Red menggunakan Algoritme Watershed berbasis Raspberry Pi - Salsabiil Hasanah; Hurriyatul Fitriyah; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Oranges contain vitamin C and a lot of mineral content. The public will definitely choose an orange fruit whose skin color is orange or the condition is ripe. Therefore, farmers must harvest citrus fruit when the conditions are ripe or when the color of the skin turns orange. In the area of ​​agriculture today there are those who implement modern agriculture. The use of technology applied to agriculture is the use of robots. Currently in Indonesia there is no robot that automatically harvests mature oranges in the garden by detecting which ones are already ripe in the garden and then picking them. The harvest process also requires a counter function of ripe oranges in the garden which can be detected to find out the number of ripe oranges found in the garden. From the problems above, the research conducted by this writer will focus on the detection of mature oranges in the garden and the calculation of mature oranges detected using digital image processing. This system will take pictures of oranges found in the garden. The process of detecting ripe oranges uses the Hue, Saturation and Chrominance-Red color space, whereas for the calculation of ripe oranges detected using a watershed algorithm. In testing the system in the process of calculating ripe oranges using watershed algorithm obtained an accuracy rate of 82.14% with an average computing time of 2652 ms for one calculation process.